1995
DOI: 10.1111/j.1540-8183.1995.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Aortic Valvuloplasty in the First Year of Life

Abstract: Between February 1988 and September 1993 balloon aortic valvuloplasty was attempted in 33 consecutive patients in the first year of life: 20 patients (61%) were younger than 1 month. Major associated anomalies such as mitral stenosis, coarctation, and hypoplastic left ventricle were found in 11 cases (33%). The balloon dilation of the aortic valve was accomplished through the right carotid cut-down approach in neonates and patients with body weight < 5 kg, through a percutaneous femoral approach in the others;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Balmer et al showed aortic regurgitation following ballooning to be the main indication for surgical aortic valve reintervention in neonates, with this being the indication in 6 out of 11 reinterventions in their neonatal patients. Other studies also confirm that aortic regurgitation remains the main indication of reinterventions following aortic valvuloplasty . In our study population, there was no significant relationship found between the degree of aortic regurgitation following valvuloplasty and need for reinterventions.…”
Section: Discussionsupporting
confidence: 85%
“…Balmer et al showed aortic regurgitation following ballooning to be the main indication for surgical aortic valve reintervention in neonates, with this being the indication in 6 out of 11 reinterventions in their neonatal patients. Other studies also confirm that aortic regurgitation remains the main indication of reinterventions following aortic valvuloplasty . In our study population, there was no significant relationship found between the degree of aortic regurgitation following valvuloplasty and need for reinterventions.…”
Section: Discussionsupporting
confidence: 85%
“…Retrograde catheterization via the umbilical artery or vein is restricted to a few days after birth and leads to difficult catheter manipulation [164] but is still favored by some cardiologists [165,166]. Using the femoral artery may leave up to 65% of the femoral arteries occluded [156], apparently without major consequences, so that some cardiologists use the right carotid artery to introduce the catheter [167][168][169][170]. However, other institutions have experienced femoral artery complications in fewer than 10% of patients [49,171].…”
Section: Late Mortalitymentioning
confidence: 99%
“…Early mortality ranges from 0 to 34% with a median of 25% (Fig. 24.3) and does not differ substantially from surgical mortality over the same period [34,75,139,156,157,160,168,[176][177][178][179][180][181][182][183][184]. Late survival and event-free survival after the procedure are shown in Fig.…”
Section: Late Mortalitymentioning
confidence: 99%
See 2 more Smart Citations